Evaluation of the role of common vetch (Vicia sativa L.) green manure in crop rotations - Pál, Vivien; Zsombik, László (Acta Agraria Debreceniensis, 2022)
Common vetch (Vicia sativa L.) is an annual legume, grown as green manure provide rapid soil cover, can increase soil moisture and organic matter content and reduce soil erosion during fall. During the fallow period, legumes grown as catch crops are known by releasing large amounts of mineral nitrogen (N) for the subsequent crop. By taking advantage of these benefits, it is possible to increase the yield of the next crop in an environmentally friendly and sustainable way. The goal of this study was to determine the value of common vetch as a green manure, considering its effect on soil conditions and the yield of next crops. We examined three different common vetch seed rate as a green manure in a crop rotation with triticale, oat and corn. Next to the green manured treatments, we used fertilized and bare fallow control treatment for comparison. In our study we evaluated the aboveground biomass weight of spring vetch green manure and its effect on the moisture content of the soil. We examined the green manure’s effect on the next crops plant height and yield. We found that the moisture content of the green manured plots was significantly higher during summer drought. On the green manured plots, 37.9% higher triticale yield, 50% higher oat yield and 44% higher corn yield were measured compared to the control plots. The insertion of spring vetch green manuring into crop rotations could be a good alternative to sustainable nutrient replenishment methods. It can be used to reduce the input needs of farming, reduce carbon footprint, contribute to the protection of soils and increase the organic matter content of the soil.